Critical Review of Teaching and Learning Methodologies for Learners with Special Educational Needs in the 21st Century and Beyond - Monique J. Grant Coke (Journal of Child and Adolescent Psychiatry, 2021)
The number of children with SEN is continuously growing, leading to pressure on the few special schools available in the USA. Furthermore, the adoption of a special school system has been criticized on the basis that it isolates and discriminates against children with special educational needs and disabilities. Even though inclusive education can address such limitations, the application of the most appropriate pedagogical approaches for SEN learners is still a challenge. The presented study focused on critically appraising the pedagogical approaches for SEN learners in the 21st century and beyond. In order to achieve this goal, a systematic review of the literature approach was adopted. The literature search process was conducted on three databases: Education Full Text, Linguistics and Language Behavior Abstracts, and PsycINFO. The selection of these databases was influenced by their reputation of hosting high quality and up-to-date literature about special education. The initial literature search process generated 6129 hits, but only ten studies were finally selected for review after the application of inclusion and exclusion criteria. A critical review of the evidence presented in the selected studies generated eight themes describing various pedagogical approaches for special education, within both blended and mainstream learning environment. Knowledge generated in this systematic review can be used by the special education sector of the U.S to develop pedagogical approaches for SEN students, leading to improved performance and social skill development.
Keywords: special educational needs